2014
DOI: 10.1155/2014/534915
|View full text |Cite
|
Sign up to set email alerts
|

Use of Antimicrobial Films and Edible Coatings Incorporating Chemical and Biological Preservatives to Control Growth ofListeria monocytogeneson Cold Smoked Salmon

Abstract: The relatively high incidence of Listeria monocytogenes in cold smoked salmon (CSS) is of concern as it is a refrigerated processed food of extended durability (REPFED). The objectives of this study were to compare and optimize the antimicrobial effectiveness of films and coatings incorporating nisin (Nis) and sodium lactate (SL), sodium diacetate (SD), potassium sorbate (PS), and/or sodium benzoate (SB) in binary or ternary combinations on CSS. Surface treatments incorporating Nis (25000 IU/mL) in combination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 68 publications
1
18
0
Order By: Relevance
“…As a result, coatings based on proteins, polysaccharides and lipid materials have been recently applied as antimicrobial active packaging systems to extend the shelf-life of seafood by the reduction of pathogenic microorganisms at their surface [106]. In this context, important results have been reported to control the proliferation of L. monocytogenes on cold smoked salmon [107]. Neetoo et al [108] also found that alginate coatings supplemented with 2.4% sodium lactate and 0.25% sodium diacetate solutions significantly delayed the growth of L. monocytogenes during a 30-day storage at 4 • C on cold-smoked salmon slices and fillets.…”
Section: Fish Productsmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, coatings based on proteins, polysaccharides and lipid materials have been recently applied as antimicrobial active packaging systems to extend the shelf-life of seafood by the reduction of pathogenic microorganisms at their surface [106]. In this context, important results have been reported to control the proliferation of L. monocytogenes on cold smoked salmon [107]. Neetoo et al [108] also found that alginate coatings supplemented with 2.4% sodium lactate and 0.25% sodium diacetate solutions significantly delayed the growth of L. monocytogenes during a 30-day storage at 4 • C on cold-smoked salmon slices and fillets.…”
Section: Fish Productsmentioning
confidence: 99%
“…In this case, lactoperoxidase (LPO) is one of the most important enzymes used as a natural antimicrobial agent, since it has a broad antimicrobial spectrum, showing bactericidal effect on Gram-negative bacteria, a bacteriostatic effect on Gram-positive bacteria, antifungal and antiviral activities [107]. LPO (5% v/v) was coated onto a chitosan matrix (1.5% w/v), showing significant reduction in Shewanella putrefaciens, Pseudomonas fluorescens and psychrotrophic and mesophilic bacteria.…”
Section: Fish Productsmentioning
confidence: 99%
“…; Gao, He et al . ; Ran, Carrias, Williams, Capps, Dan, Newton, Kloepper, Ooi, Browdy, Terhune & Liles ; Masso‐Silva & Diamond ), salmon (Belhaj, Desor, Gleizes, Denis, Arab‐Tehrany, Soulimani & Linder ; Neetoo & Mahomoodally ) and zebrafish (Lin, Liu, Hu & Zhang ; Zhao, Dai & Jin ; Jheng, Lee, Ting, Pan, Hui & Chen ; Wang, Meng et al . ; Wang, Chang et al .…”
Section: Biological Factorsmentioning
confidence: 99%
“…The development of edible coatings and natural preservatives with high antioxidant and antibacterial activities that prolong the shelf life of food has been extensively studied (Albertos et al, 2015;Alsaggaf et al, 2017;Jasour, Ehsani, Mehryar, & Naghibi, 2015;Li et al, 2013;Li et al, 2017;Neetoo & Mahomoodally, 2014;Raeisi et al, 2015;Zhang, Li, Dong, Zhi, & Zong, 2016). To the best of our knowledge, however, the use of SA infused with TP for fish preservation has not been explored.…”
Section: Introductionmentioning
confidence: 99%